LIBRA - a differentiated view on Facebook's virtual currency project - Volker Brühl (Goethe University Frankfurt, Center for Financial Studies (CFS), 2019)
Libra - a global virtual currency project initiated by Facebook - has been the subject of many controversial discussions since its announcement in June 2019. This paper provides a differentiated view on Libra, recognising that different development scenarios of Libra are conceivable. Libra could serve purely as an alternative payment system in combination with a dedicated payment token, the Libra coin. Alternatively, the Libra project could develop into a broader financial infrastructure for advanced financial services such as savings and loan products operating on the Libra blockchain. Based on a comparison of the Libra architecture with other cryptocurrencies, the opportunities and challenges for the development of the respective Libra ecosystems are investigated form a commercial, regulatory and monetary policy perspective.
urn:nbn:de:hebis:30:3-515946
Keywords: E42; E52; G20; 330